Loss of calibre information during vessel segmentation - Che Azemin, Mohd Zulfaezal; Kumar, Dinesh Kant; Aliahmad, Behzad; Hao, Hao (2012)
To obtain precise calibre measurements, there are two general approaches: segment the vessels and measure the diameter, and to measure the diameter from the greyscale images. While there is a claim that vessel segmentation does not solve diameter measurement problems it has not been proven experimentally. The aim of this work is two-fold: first, to prove that the resulting edges from good vessel segmentation may not be suitable for precise diameter measurement, and, second, to propose a method for compensating for the imprecision in the calibre measurement from the segmentation.